1999
DOI: 10.1097/00000372-199908000-00004
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study of Basal Cell Carcinoma and Trichoepithelioma

Abstract: The histologic distinction between tricheopithelioma and basal cell carcinoma may be difficult in small biopsies. Immunohistochemical stains have been used to help make this distinction; however, published studies have generally been limited to a few antibodies. To this end we performed a comprehensive immunohistochemical analysis of 20 basal cell carcinomas and 10 tricheopitheliomas from our files, in search of a consistent pattern of reactivity to distinguish the neoplasms in biopsies. The antibodies used we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 14 publications
1
70
2
2
Order By: Relevance
“…[7][8][9][10] The diffuse staining of bcl-2 in tumor nests of basal cell carcinoma and peripheral staining of tumor nests in cases of trichoepithelioma reported in some studies was refuted by others claiming that the differential expression pattern at the periphery compared with the center of lesional aggregates cannot be assessed reliably, as the epithelial strands are usually thin in the desmoplastic variants of both neoplasms. 3,[9][10][11][12] Use of expression of the AR, initially shown by Izikson et al, were later reproduced by Costache et al 3 Both groups showed AR expression in 475% of basal cell carcinomas tested and lack of the same in both trichoepithelioma and desmoplastic trichoepithelioma. 15 Undermining these results were those obtained by Katona et al who found AR expression in only 65% of basal cell carcinomas tested and also showed AR positivity in 13% of desmoplastic trichoepitheliomas in their series.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[7][8][9][10] The diffuse staining of bcl-2 in tumor nests of basal cell carcinoma and peripheral staining of tumor nests in cases of trichoepithelioma reported in some studies was refuted by others claiming that the differential expression pattern at the periphery compared with the center of lesional aggregates cannot be assessed reliably, as the epithelial strands are usually thin in the desmoplastic variants of both neoplasms. 3,[9][10][11][12] Use of expression of the AR, initially shown by Izikson et al, were later reproduced by Costache et al 3 Both groups showed AR expression in 475% of basal cell carcinomas tested and lack of the same in both trichoepithelioma and desmoplastic trichoepithelioma. 15 Undermining these results were those obtained by Katona et al who found AR expression in only 65% of basal cell carcinomas tested and also showed AR positivity in 13% of desmoplastic trichoepitheliomas in their series.…”
Section: Discussionmentioning
confidence: 93%
“…Immunohistochemical markers putatively useful in reliably differentiating trichoepithelioma (and/or trichoblastoma) and basal cell carcinoma in general and desmoplastic trichoepithelioma and morpheaform/infiltrative basal cell carcinoma in particular include CD34, Bcl-2, CK20, and AR. 3,[7][8][9][10][11][12][15][16][17] Positive peritumoral staining of trichoepithelioma and desmoplastic trichoepithelioma by CD34, shown by Kirchmann et al, in 100% of cases of both with negative staining in all cases of basal cell carcinoma was contradicted by subsequent studies that showed positive peritumoral staining in some cases of basal cell carcinoma and absence of the same in cases of trichoepithelioma. [7][8][9][10] The diffuse staining of bcl-2 in tumor nests of basal cell carcinoma and peripheral staining of tumor nests in cases of trichoepithelioma reported in some studies was refuted by others claiming that the differential expression pattern at the periphery compared with the center of lesional aggregates cannot be assessed reliably, as the epithelial strands are usually thin in the desmoplastic variants of both neoplasms.…”
Section: Discussionmentioning
confidence: 94%
“…However, in the literature, diffuse Bcl-2 expression by basaliomatous cells was observed in basal cell carcinoma tumors, while expression of this marker only in the outermost layers of basaloid nests was observed in trichoepithelioma tumors; this difference in Bcl-2 localization was considered feasible for the discrimination between these two basaloid tumors. [15][16][17][18] Trichoepithelioma and basal cell carcinoma tumors displayed different epithelial membrane antigen staining patterns. However, epithelial membrane antigen expression did not reach significant 'Beta' values in the regression analysis.…”
mentioning
confidence: 99%
“…Other authors built panels with epithelial markers or the association of epithelial and stromal markers. 11,12,16 In this work, the more effective panel was built using data obtained from a linear regression analysis and was composed of at least one marker displaying stromal labeling.…”
mentioning
confidence: 99%
“…Immunohistochemistry techniques (33) and lectin staining (3,27) have been tested as supporting tools for differential diagnosis for skin lesions.…”
Section: Introductionmentioning
confidence: 99%